The Vascular Wall State and Microcirculation Parameters in Patients with Controlled and Uncontrolled Arterial Hypertension - V. I. Podzolkov; A. E. Bragina; D. U. Natkina; T. A. Safronova; N. N. Nebieridze; E. V. Podshibyakina (Рациональная фармакотерапия в кардиологии)
Aim. To study the rigidity of the vascular wall and microcirculation parameters in patients with uncontrolled (UCAH) and controlled arterial hypertension (CAH).Material and methods. 134 patients with essential hypertension were included, among them 88 (65.7%) patients with UCAH and 46 (34.3%) patients with CAH. Patients in both groups were similar by sex, age, duration of hypertension and some biochemical parameters. Patients had a study of the parameters of stiffness of the vascular wall, microcirculation parameters, as well as an evaluate of the plasma level of asymmetric dimethylarginine (ADMA).Results. Pulse wave velocity (PWV) did not differed between the UCAH and CAH, both in absolute values (1144 [1000-1290] vs 1138 [10281279] cm/sec; p=0.385) and in the frequency of exceeding the normal values (95% vs 92%; p=0.784). Microcirculation index (MI) in CAH was significantly higher than in the UCAH group: 30.55 [27.08-34.4] and 22.82 [18.62-26.05], respectively (p <0.05). ADMA plasma concentration was significantly higher 0.69 [0.62-0.81] μmol/l in UCAH, than in the CAH group 0.62 [0.58-0.70] µmol/l (p <0.05), that shows the presence of endothelial dysfunction. There were detected significant relation between MI and cognitive status.Conclusion. The results of our study indicate the presence of signs of endothelial dysfunction in patients with UCAH with changes in the stiffness of the vascular wall comparable with the CAH group. This may reflect the slower effect of antihypertensive therapy on the remodeling processes of large vessels in comparison with the microvasculature.